FORMULATION OF BUSINESS STRATEGY USING SWOT METHOD AND QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM): (CASE STUDY SURYA BOUTIQUE HOTEL SEMARANG) - Risma Nor Safitri; Siti Arbainah; Tutik Dwi Karyanti (Politeknik Negeri Semarang, 2023)
This research is a qualitative descriptive study that aims to formulate a business strategy at Surya Boutique Hotel Semarang by collecting data through observation, interviews, and questionnaires. Data analysis was carried out using IFE, EFE, CPM, SWOT, and QSPM which showed the results of an IFE weighted score is 2,644, an EFE weighted score is 3,258, and a CPM score is 3,023 which means the company is in a strong enough position in controlling the strengths and weaknesses to face opportunities and threats. Based on the SWOT analysis, integration, intensive, and diversification strategies were developed into 8 alternative strategies for the company. The most suitable strategy based on QSPM is to rearrange the number of room availability based on customer interest with a TAS value of 6,968. This strategy is in line with the current condition of the hotel, which is experiencing a limited number of rooms in the type that consumers are most interested in.